Ecological Observations on the Fern Flora of Thannamandi District Rajouri, Jammu & kashmir, India - Anjum, Shagufta; Pant, Shreekar; Pande, H. C.; Rinchen, Tsewang (Indian Forester, 2014)
Thannamandi one of the biodiversity rich areas of district Rajouri, covers a total area of 229 km2 . The altitude ranges between 1100 - 2000 m and supports sub-tropical to temperate vegetation and offers congenial climatic conditions favourable for luxuriant growth of the vegetation including ferns. Field collections were made from 2012 to 2013 for the assessment of Pteridophytic diversity and their ecology attributes. Ferns of the selected area are divided into 04 major ecological categories which are further sub categorized into sub-categories. Lithophytic ferns are more in number followed by terrestrial, epiphytic and hydrophytic. Altitudinal distribution of pteridophytes reveals that number of species varies from lower to higher altitude. With altitudinal range as maximum number of species present in higher altitude and then keeps on decreasing towards lower altitude. Further, based on our surveys and analysis conservation of board leaved communities are also suggested as it is the store house of such vital wealth.